Innovation and Quality Improvement in The Palm Oil Industry to Maintain Indonesia's Export Competitiveness - Judijanto, Loso; Hamdani, Hamdani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The palm oil industry is one of Indonesia’s most strategic export sectors, yet its competitiveness in the global market is increasingly challenged by rising quality standards, sustainability requirements, and international competition. This study aims to analyze the effect of innovation and quality improvement on maintaining Indonesia’s palm oil export competitiveness. A quantitative research approach was applied using primary data collected from 85 palm oil farmers through a structured questionnaire measured on a Likert scale. The data were analyzed using SPSS version 25, employing descriptive statistics, validity and reliability tests, and multiple linear regression analysis. The results indicate that innovation has a positive and significant effect on export competitiveness, while quality improvement shows a stronger positive and significant influence. These findings suggest that farmers who adopt new technologies, improve cultivation practices, and maintain consistent product quality are more capable of meeting global market demands. Simultaneously, innovation and quality improvement significantly explain variations in export competitiveness, with the model accounting for 50.8 percent of the variance. This study highlights the importance of strengthening innovation capacity and implementing continuous quality enhancement at the farmer level to sustain Indonesia’s competitive position in the global palm oil market. The findings provide practical implications for policymakers and industry stakeholders in designing programs that support technological adoption and quality-based development strategies.